The Use of Traditional Plant Remedies in Hoshiarpur District of Punjab, India - Ahluwalia, M.C. Sidhu*, Kuljinder Kaur; A. S. (Journal of Phytology, 2011)
The present investigation was carried out in Hoshiarpur district of Punjab to understand the use of medicinal plant species for various curative purposes. The study was undertaken through semi structured questionnaire. About 110 plant species belonging to 97 genera and 51 families were documented. Altogether 40 types of ailments have been taken care of by using these plant species. Leaves were the most useful part as compared to other plant parts for the treatment of various ailments. This is followed by fruits and seeds. Most of the remedies were prepared as mixtures of plants/plant parts to cure diseases like diarrhoea, cough & cold, vomiting etc. Informants were randomly selected irrespective of their sex between the ages of 30-95years. During investigation, it has been observed that the trend of traditional plant remedies is declining gradually.